SPECIFIC CHARACTERISTICS OF UZBEK NATIONAL ART OF EMBROIDERY - Mamaxanova, Zebuniso (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article describes the modern development directions of embroidery based on the study of the unique features of the Uzbek national embroidery art. The directions of modern development of embroidery have been determined based on research with students studying design.